Cyclosporine A mediates Pathogenesis of Aggressive Cutaneous Squamous Cell Carcinoma by Augmenting Epithelial-Mesenchymal Transition: Role of TGF-β Signaling Pathway - Walsh, Stephanie B. (2011)
Organ transplant recipients (OTRs) develop multiple aggressive and metastatic non-melanoma skin cancers (NMSCs). Yet, the underlying mechanism remains elusive. Employing a variety of immune-compromised murine models, immunoblotting, immunohistochemical and immunofluorescence techniques, we show that human squamous xenograft tumors in nude mice grow faster and become significantly larger in size following treatment with the immunosuppressive drug, cyclosporine A (CsA). Re-injected tumor cells isolated from CsA-treated xenografts continued to form larger tumors in nude mice than those from vehicle-controls and retained the CsA-signatures of calcineurin signaling inhibition. Similar results were obtained when these tumors were grown in SCID-beige mice or in immuno-competent mice inoculated with syngeinic tumor cells. Consistently, tumors in the CsA group manifested enhanced cellular proliferation and decreased apoptosis. Tumors in CsA-treated animals also showed an augmented epithelial-mesenchymal transition (EMT) characterized by an increased expression of fibronectin, α-SMA, vimentin, N-cadherin, MMP-9/-2, snail and twist with a concomitant decrease in E-cadherin. CsA-treated xenograft tumors manifested increased TGFβ1 expression and TGFβ-dependent signaling characterized by increased nuclear p-Smad2/3. Our data demonstrate that CsA alters the phenotype of skin SCCs to an invasive and aggressive tumor-type by enhancing expression of proteins regulating EMT acting through the TGFβ1 signaling pathway providing at least one unique mechanism by which multiple aggressive and metastatic NMSCs develop in OTRs.